2001
DOI: 10.1038/nm1201-1306
|View full text |Cite
|
Sign up to set email alerts
|

A novel influenza A virus mitochondrial protein that induces cell death

Abstract: While searching for alternative reading-frame peptides encoded by influenza A virus that are recognized by CD8+ T cells, we found an abundant immunogenic peptide encoded by the +1 reading frame of PB1. This peptide derives from a novel conserved 87-residue protein, PB1-F2, which has several unusual features compared with other influenza gene products in addition to its mode of translation. These include its absence from some animal (particularly swine) influenza virus isolates, variable expression in individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

38
982
3
8

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 906 publications
(1,039 citation statements)
references
References 23 publications
38
982
3
8
Order By: Relevance
“…Recombinant viruses, WT HKx31 and mutant HKx31(–NP –PA –F2) (TKO), and HKx31(–NP –PA –F2 –PB1 –NS2) (QKO) were generated, using the eight‐plasmid reverse genetics system described previously for the mutation of the D b NP 366–374 and D b PA 224–233 epitopes 47, 48. In the TKO viruses, the WT D b PB1‐F2 62–70 epitope (LSLRNPILV was changed to LSLRQPILV 49. In the QKO virus, the WT K b PB1 703–711 epitope (SSYRRVPGI) was changed to SSFRRVPGI, and the WT K b NS2 114–121 epitope (RTFSFQLI) was changed to RTFSAQLI.…”
Section: Methodsmentioning
confidence: 99%
“…Recombinant viruses, WT HKx31 and mutant HKx31(–NP –PA –F2) (TKO), and HKx31(–NP –PA –F2 –PB1 –NS2) (QKO) were generated, using the eight‐plasmid reverse genetics system described previously for the mutation of the D b NP 366–374 and D b PA 224–233 epitopes 47, 48. In the TKO viruses, the WT D b PB1‐F2 62–70 epitope (LSLRNPILV was changed to LSLRQPILV 49. In the QKO virus, the WT K b PB1 703–711 epitope (SSYRRVPGI) was changed to SSFRRVPGI, and the WT K b NS2 114–121 epitope (RTFSFQLI) was changed to RTFSAQLI.…”
Section: Methodsmentioning
confidence: 99%
“…Compared to the full-length PB1-F2, this protein is unlikely to be functional. As a pro-apoptotic factor, PB1-F2 plays an important role in viral pathogenicity both in vitro and in vivo (Chen et al, 2001;Zamarinet et al, 2006). In addition, PB1-F2 increases susceptibility to secondary bacterial pneumonia in mice (McAuley et al, 2007).…”
Section: The Human-infecting H6n1 Infl Uenza Virus Has a Truncated Pbmentioning
confidence: 99%
“…Segments A-D of the protein represent, respectively, the amphipathic a-helical domain, the transmembrane domain, the hinge region and the C-terminal beta sheet hairpin. Panel C also shows a more detailed helical wheel model of the amphipathic a-helical domain of p13 (amino acids [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. Panel C does not indicate the matrix and intermembrane space faces of the inner membrane, as the topology of p13 has not been defined.…”
Section: Amino Acid Sequence and Structural Features Of Htlv-1 P13mentioning
confidence: 99%
“…Immuno-electron microscopy and sub-mitochondrial fractionation experiments demonstrated that the majority of p13 is inserted as an integral membrane protein in the inner mitochondrial membrane [6]. The mitochondrial targeting of p13 is directed by an atypical mitochondrial targeting sequence (MTS) formed by 10 amino-proximal residues (amino acids [21][22][23][24][25][26][27][28][29][30] that are contained within the a-helix described above [7], with four arginines in the MTS conferring amphipathic properties to the helix. In contrast to canonic MTSs, the targeting signal of p13 is not cleaved upon import into mitochondria [7].…”
Section: Intracellular Localization Of P13mentioning
confidence: 99%
See 1 more Smart Citation